Tahapan Penyusunan Dokumen Rencana Pengamanan Air Minum di Sistem Penyediaan Air Minum (SPAM) Kota Cimahi - Dewi, Arynda; Rachmawati Sugihhartati Dj (Jurnal Serambi Engineering, 2026)
Possessing of safe drinking water is crucial for sustainable health development. Deteriorating water quality can endanger human health, one of which is diarrhea caused by water contaminated with E. coli bacteria. This study aims to develop a RPAM document to determine strategies for reducing the risk of hazardous events in all SPAM components. The methods used for this study were observational studies and literature reviews. The study concluded that the preparation of the RPAM document focuses on priority risks and proactively monitors protective measures designed to protect the water supply. Through the preparation of the RPAM document, it is also expected that customer complaints about water quality will be significantly reduced.